Unmet supportive care needs of head and neck cancer survivors: A scoping review - Ya Huang; Lan Chen; Mi Zeng; Jingjing Wu; Yan Lu; Huiru Zhang; Xiaoshan Li; Huijun Quan; Guqing Zeng (PLoS ONE, 2026)
Aim To investigate the unmet supportive care needs, the existing tools to screen these unmet needs, and the factors associated with them among head and neck cancer survivors. Methods A systematic search was conducted across eleven databases, including Web of Science and PubMed. The search covered the period from the inception of each database up to August 20, 2025. Identified records were screened for relevance, followed by data extraction and analysis. Results A total of 4074 articles were identified, of which 12 were included. 7 assessment tools were identified. Among these, 3 offered a relatively comprehensive scope, 2 focused specifically on disease-functional needs, and 1 incorporated the disease -lifestyle needs. Head and neck cancer survivors reported unmet supportive care needs across health system/information, psychological, patient care/support, physical/daily living, sexuality, disease-specific functioning and disease-specific life. Health system/information, patient care/support, psychological needs are the top three unmet needs. Some demographic, clinical, and psychological factors are associated with these unmet needs. Conclusion Head and neck cancer survivors experience considerable unmet supportive care needs in health system/information, psychological and patient care/support. Existing assessment tools lack comprehensiveness, failing to integrate both universal and disease-specific needs. Future development of a multidimensional, integrated tool is essential. Such instruments will enable multidisciplinary teams to deliver personalized support care informed by assessment results.